METHODOLOGY OF FORMING INTERDISCIPLINARY COMPETENCES IN HIGHER EDUCATION BASED ON THE INTEGRATION OF STEAM APPROACH AND DIGITAL TECHNOLOGIES - Vafayeva Zarrina Xashimovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This thesis explores the methodology of developing students’ interdisciplinary competences by integrating the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach and digital technologies within the higher education system. Based on the case of students from the Faculty of English, the opportunities for implementing cross-disciplinary projects and enriching the language learning process through technological and creative approaches are analyzed. Drawing from experimental research, the growth dynamics of students’ analytical thinking, designing, and digital tool usage skills are illustrated through quantitative indicators, and relevant methodological recommendations are formulated.